Comparative study of sutureless thyroidectomy using harmonic scalpel versus vessel ligation thyroidectomy - Kala, Sonal; Kaintura, Madhuri; Maithani, Tripti; Varma, Arvind; Dogra, Rishabh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Hemostasis is crucial for thyroidectomy surgery. Traditional methods used for hemostasis like suture ligation has a risk of knot slipping hence new methods of ligation became need of the hour. Harmonic scalpel is one such newer method of vessel ligation providing faster and precise ligation of vessels. The objective was to compare effectiveness of sutureless technique using harmonic scalpel in thyroid surgery with conventional suture ligation technique. Methods: The 50 patients undergoing thyroid surgery were divided into two groups of 25 each. Group A underwent thyroid surgery using conventional suture ligation and group B underwent thyroid surgery using harmonic scalpel. Results: Our results showed that in group B, none of the patients had change of voice and only 1 had transient hypocalcemia while 2 in group A had recurrent laryngeal paresis and 4 had transient hypocalcemia (not statistically significant). The average blood loss was less in group B as compared to group A (p=0.014), as was the post op drain collection 12.60 ml (p=0.034) as compared to 17.80 ml in group A, and the operative time 34.60 minutes (p=0.00) as compared to 45.44 minutes in group A. The overall cost was thus conspicuously reduced as compared to group A. Conclusion: Sutureless thyroidectomy using harmonic scalpel is safe, fast and cost-effective technique to perform thyroidectomies.